UPAYA PENINGKATAN NILAI TAMBAH PRODUK HORTIKULTURA DI DESA BALUNIJUK, KECAMATAN MERAWANG KABUPATEN BANGKA - Sitti Nurul Aini (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2016)
Balunijuk Village is one of the centers of horticultural crop production in the Bangka Belitung Islands Province. The agricultural system of horticultural crops in this village is classified as conventional and there are still problems. Community service activities carried out in Balunijuk Village basically aim to overcome the problems that exist in the village. The main problems faced are horticultural agriculture which is less profitable due to expensive agricultural inputs and the perishable nature of horticultural products. The activities that are the solution to overcome these problems are: making compost based on vegetable waste, post-harvest handling of horticultural products, integrated pest control and terrarium making. The implementation of community service activities was welcomed by villagers and farmers in Balunijuk Village because it was felt to provide benefits in the future. The implementation of community service activities in Balunijuk Village needs to be continued to assist the sustainability of the programs that have been implemented.